2024
DOI: 10.1186/s13048-024-01354-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of polyphenols in remodeling the host gut microbiota in polycystic ovary syndrome

Ping Zhou,
Penghui Feng,
Baoying Liao
et al.

Abstract: Polycystic ovary syndrome (PCOS) is a common reproductive and metabolic condition in women of childbearing age and a major cause of anovulatory infertility. The pathophysiology of PCOS is complex. Recent studies have reported that apart from hyperandrogenism, insulin resistance, systemic chronic inflammation, and ovarian dysfunction, gut microbiota dysbiosis is also involved in PCOS development and may aggravate inflammation and metabolic dysfunction, forming a vicious cycle. As naturally occurring plant secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 110 publications
0
1
0
Order By: Relevance
“…Recent studies have shown that gut microbiota dysbiosis is also involved in the development of PCOS and may exacerbate inflammation and metabolic disorders. Polyphenols and their metabolites have been shown to have anticancer, antibacterial, vasodilatory, and analgesic properties, which significantly alleviate systemic chronic inflammation occurring in women with PCOS [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown that gut microbiota dysbiosis is also involved in the development of PCOS and may exacerbate inflammation and metabolic disorders. Polyphenols and their metabolites have been shown to have anticancer, antibacterial, vasodilatory, and analgesic properties, which significantly alleviate systemic chronic inflammation occurring in women with PCOS [ 7 ].…”
Section: Introductionmentioning
confidence: 99%